Prenatal developmental toxicity of crocus sativus (saffron) in wistar rats - Edamula, Ramesh; Deecaraman, M; Santhosh Kumar, Dharmapura; Krishnamurthy, Heggnahalli; Latha, Madaigowda (International Journal of Pharmacology and Toxicology, 2014)
The prenatal developmental toxicity of Crocus sativus (saffron) was evaluated in a mammalian species taking Wistar rat as the model. Saffron administered as an oral gavage from Day 5 of gestation (day of implantation) until Day 19 of gestation at the doses of 50, 250 and 1000 mg/kg/day did not elicit  any effects on maternal body weight gains, food intake, gravid uterine weight, corpora lutea and implantation counts, pre and post implantation loss, litter size, weight and length. No abnormalities in the fetuses were noticed when subjected to external, soft tissue and skeletal examinations. The results obtained conclude that saffron did not induce maternal toxicity and structural and / or other abnormalities in the fetus and hence saffron is considered to have no teratogenic potential. Keywords: Abnormalities, Fetus, Litter, Saffron, Skeletal.